Fundamental investigation on the attraction behavior of household ants to caffeine in coffee. - Ab Majid, Abdul Hafiz (Universiti Sains Malaysia, 2015)

(untitled)
From the field sampling, the most dominant household ants are P. longicornis (22.09%),T.indicum (17.74%), T. melanocephalum (17.00/0), M. pharaonis (10.61%), and Pheidole spp. (5.22%). Extracts from Arabical Robusta and Liberica coffee showed an influence on the behavior of Tapinoma indicum (TI),Monomorium pharaonis (MP) and Solenopsis geminata (SG) workers, but the clearest effect was seen with Arabica in olfactory bioassay.